HIV induced nitric oxide and lipid peroxidation, influences neonatal birthweight in a South African population. (December 2018) - Anderson, Samantha M.; Naidoo, Rajen N.; Pillay, Yashodani; Tiloke, Charlette; Muttoo, Sheena; Asharam, Kareshma; Chuturgoon, Anil A.
Abstract: HIV has been implicated in adverse birth outcomes, due to increased oxidative stress and inflammation. In addition, HIV has been reported to increase nitric oxide levels. Therefore the combined exposures to HIV and traffic-related air pollution, within South Durban, South Africa (SA), may lead to adverse birth outcomes. However, the exact mechanism is still unknown; this study aimed to identify a potential mechanism. First, the influence of HIV on oxidative and nitrosative stress markers in pregnant women was assessed. Secondly, the effect of these stress makers and exposure to oxides of nitrogen (NOx) on neonatal birthweight (BW) was evaluated. Finally, the effect HIV and traffic-related pollution exposure has on the oxidative and endoplasmic profile and epigenetic regulation of Nrf2-Keap1 pathway by miR-144 and miR-28 in pregnant women was determined. Women, in their third trimester with singleton pregnancies, who were HIV+ and HIV−, were recruited from Durban, SA. Biomarker levels of serum nitrites/nitrates (NO) and malondialdehyde (MDA) were analysed and mRNA expression levels of oxidative and endoplasmic stress response genes were assessed. Land regression modelling was performed to determine NOx exposure levels. HIV exposure during pregnancy was associated with increased NO levels. NO was shown to reduce neonatal BW. NO and MDA was found to reciprocally increase each other, with HIV differentially influencing MDA's effect on BW. HIV down-regulated miR-144 which was negatively associated with Nrf2, suggesting a potential mechanism for HIV associated chronic oxidative stress. This study proposes that NO plays a key role in neonatal BW reduction in response to HIV and traffic-related air pollution. Highlights: HIV exposure increased serum NO, with reciprocal action on MDA levels. HIV and NOx exposure induced miR-144, suggested as a mechanism for increased oxidative stress. Exposure to heavy pollution in south Durban activated the ER stress response. Maternal serum NO reduced neonatal birthweight, in heavily polluted Durban south.